2018
DOI: 10.3390/polym10040462
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of Chitosan and Its Derivative Nanoparticles

Abstract: Chitosan is a biodegradable natural polymer with many advantages such as nontoxicity, biocompatibility, and biodegradability. It can be applied in many fields, especially in medicine. As a delivery carrier, it has great potential and cannot be compared with other polymers. Chitosan is extremely difficult to solubilize in water, but it can be solubilized in acidic solution. Its insolubility in water is a major limitation for its use in medical applications. Chitosan derivatives can be obtained by chemical modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
228
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(245 citation statements)
references
References 100 publications
4
228
0
13
Order By: Relevance
“…(020), (110) and (120) represent the diffraction peak characteristic at 2θ ≈ 10 • , ≈20 • , and ≈21 • , respectively. It is known that the crystalline structure of chitosan is destroyed by ionic cross-linking interactions between the amino groups on chitosan and TPP [14,30]. Depolymerization reactions could have occurred favorably through the crystalline domains of the biopolymer, resulting in a decrease in the intensity of the characteristic peaks of chitosan [36].…”
Section: Crystalline Structure Of Chitosan and Chitosan Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…(020), (110) and (120) represent the diffraction peak characteristic at 2θ ≈ 10 • , ≈20 • , and ≈21 • , respectively. It is known that the crystalline structure of chitosan is destroyed by ionic cross-linking interactions between the amino groups on chitosan and TPP [14,30]. Depolymerization reactions could have occurred favorably through the crystalline domains of the biopolymer, resulting in a decrease in the intensity of the characteristic peaks of chitosan [36].…”
Section: Crystalline Structure Of Chitosan and Chitosan Nanoparticlesmentioning
confidence: 99%
“…It is known that hydroxyl, and amino groups in chitosan are key components in eliminating anion radicals such as superoxide and hydroxyl radicals [8][9][10]12] It has been reported that the amino and hydroxyl groups on chitosan backbone represent target moieties for chemical modifications to improve the aqueous solubility of chitosan since it is soluble only in an aqueous acidic solution, which is a major hurdle for its application [5]. The unique properties of chitosan, such as nontoxicity to humans [13][14][15]; commercial accessibility, biodegradability and biocompatibility [14,15], and high mucoadhesive properties [15,16] make chitosan an excellent choice for nanoparticle assembly. Chitosan-based nanoparticles are commonly obtained by ionic gelation using the multivalent ion tripolyphosphate (TPP) [14][15][16] which possesses a large number of lone-pair electrons and high binding power with materials with empty orbitals [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of MXD depots is less reported for lipidic nanoparticles, which highlights the importance of nanocapsules in its targeted action enhancement in the hair follicles. Chitosan, a natural polymer derived from the chitin of crustaceans' exoskeletons, has been extensively investigated in nanotechnology due to its biological compatibility, degradability, adhesiveness and renewability [14,74]. Moreover, its antimicrobial and anti-inflammatory activity, along with its ability to bind with lipids, comprise important features for application in topical therapeutic treatments [75,76].…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Chitosan is a natural polysaccharide produced by deacetylation of chitin. It is non-toxic, biocompatible and biodegradable (Huang et al, 2004;Zhao et al, 2018). Chitin is the main component of crustaceans (crab, shrimp, etc.…”
Section: Introductionmentioning
confidence: 99%